Mesoscopic modelling of colloids in chiral nematics. - Ravnik, M; Alexander, G; Yeomans, J; Zumer, S (2010)
We present numerical modelling of colloidal particles in chiral nematics with cubic symmetry (blue phases) within the framework of the Landau-de Gennes free energy. The interaction potential of a single, nano-sized colloidal particle with a -1/2 disclination line is calculated as a generic trapping mechanism for particles within the cholesteric blue phases. The interaction potential is shown to be highly anisotropic and have threefold rotational symmetry. We discuss the equilibration of the colloidal texture with respect to particle positions and the unit cell size of the blue phase. We also describe how preservation of the liquid crystal volume and the number of particles allows blue phase colloidal structures with different unit cell sizes and configurations to be compared numerically.